The sacred self : a cultural phenomenology of charismatic healing - Csordas, Thomas J. (University of California Press, 1997)
How does religious healing work, if indeed it does? What is actually being healed by the performances of the shaman, the medicine man, or the faith healer? In this study of the contemporary North American movement known as the Catholic Charismatic Renewal, Thomas Csordas offers new insight into the experiential specificity that defines efficacy in therapeutic ritual performance. This is not only a book about healing, however, but also one about the phenomenology of self and self-transformation. The Catholic Charismatic Renewal is a movement that incorporates Pentecostal practices into Catholicism. In the nearly three decades since its inception, the movement has developed a system that includes several genres of healing: physical healing, emotional healing, and deliverance from evil spirits. Blending ethnographic description and detailed case studies within these various healing genres, Csordas works out a theory of self and therapeutic efficacy grounded in the notions of embodiment and orientation. With this theory he examines the experience of sensory imagery and performative utterance and explicates the sense of the sacred that is cultivated by participation in this coherent ritual system. The system in turn is embedded in the Charismatic world of meaning within which the sacred self comes into being: to be healed is to inhabit the Charismatic world as a sacred self. Csordas calls his approach "cultural phenomenology" because it is concerned with synthesizing the immediacy of embodied existence with the multiplicity of cultural meaning in which we are always and inevitably immersed. This innovative book forms the basis for a rapprochement between phenomenology and semiotics in culture theory. It will interest anthropologists, philosophers, psychologists, physicians, and students of comparative religion and healing